Reduction of losses in dual‐permanent‐magnet‐excited Vernier machine by segmented stator for electric aircraft - Jinghua Ji; Chen Jia; Wenxiang Zhao; Zhijian Ling; Yu Zeng; Zongwang Li (IET Electric Power Applications)
Abstract The authors present a low‐loss dual‐permanent‐magnet‐excited vernier (DPMEV) machine with segmented stator design to meet the requirements of low iron loss of electric aircraft based on the field modulation theory. The stator topology features and losses of both the original and segmented DPMEV machines are comparatively investigated. Then, the armature air‐gap flux density is deduced by the magnetic motive force‐permeance model, and the influence of each harmonic on the losses are analysed. It is found that the harmonic which produces losses in the original machine reduced greatly after introducing the segmented structure. Furthermore, the electromagnetic performances of two DPMEV machines are comparatively analysed by finite element analysis. Finally, two prototypes of the original and segmented DPMEV machines are built and tested to verify the theoretical analysis.